Predict initial subthalamic nucleus stimulation outcome in Parkinson's disease with brain morphology. (20th January 2022) - Chen, Yingchuan; Zhu, Guanyu; Liu, Yuye; Liu, Defeng; Yuan, Tianshuo; Zhang, Xin; Jiang, Yin; Du, Tingting; Zhang, Jianguo
Abstract: Aim: Subthalamic nucleus deep brain stimulation (STN‐DBS) has been reported to be effective in treating motor symptoms in Parkinson's disease (PD), which may be attributed to changes in the brain network. However, the association between brain morphology and initial STN‐DBS efficacy, as well as the performance of prediction using neuroimaging, has not been well illustrated. Therefore, we aim to investigate these issues. Methods: In the present study, 94 PD patients underwent bilateral STN‐DBS, and the initial stimulation efficacy was evaluated. Brain morphology was examined by magnetic resonance imaging (MRI). The volume of tissue activated in the motor STN was measured with MRI and computed tomography. The prediction of stimulation efficacy was achieved with a support vector machine, using brain morphology and other features, after feature selection and hyperparameter optimization. Results: A higher stimulation efficacy was correlated with a thicker right precentral cortex. No association with subcortical gray or white matter volumes was observed. These morphological features could estimate the individual stimulation response with an r value of 0.5678, an R 2 of 0.3224, and an average error of 11.4%. The permutation test suggested these predictions were not based on chance. Conclusion: Our results indicate that changes in morphology are associated with the initial stimulation motor response and could be used to predict individual initial stimulation‐related motor responses. Abstract : The changes in morphology are associated with the initial stimulation motor response of subthalamic nuclei deep brain stimulation and could be used to predict individual initial stimulation‐related motor responses.